Malware in Computer Systems: Problems and Solutions - Hama Saeed, Mariwan Ahmed (IJID (International Journal on Informatics for Development), 2020)
Malware is a harmful programme, which infects computer systems, deletes data files and steals valuable information. Malware can attack personal and organization computer systems. In this paper, the most recent and dangerous types of malware, including CovidLock Ransomware, have been analysed and the most suitable countermeasures of malware have been provided. The purpose of this paper is to suggest manually removing malware through a range of tools. It investigates whether the University of Halabja employees are protected against malware or not and it hypothesizes that the university of Halabja employees are not protected in a great level against malware attacks. A questionnaire has been conducted and analysed. The results of the questionnaire confirmed that the university of Halabja employees are not crucially protected. Therefore, it works to propose a sufficient way to make the whole organization protected. This research can be extended to include public and private universities across Kurdistan region in order to identify the most secure university in this region against malware attacks.